Ideas of sustainable development in the content of science disciplines - Dzyatkovskaya, Elena N. (Journal of the Belarusian State University. Ecology, 2021)
The article deals with the role of science education in explaining the modern environmental crisis and ways out of it.The urgency and peculiarities of education for sustainable development, its challenges to updating the content of natural science disciplines are considered. The directions of such updating are justified: reflection of modern state of science, fundamentality of knowledge, its interdisciplinary integration and worldview orientation. The conclusion is made that for understanding the interdisciplinary concept of sustainable development the set of special scientific pictures of the world is not enough. The problem of developing a natural-science picture of the world as an environmental component of education for sustainable development is posed. The article considers the basic categories of synthesis of natural-science knowledge into the natural-science picture of the world: nature, material unity of the world, development, system, self-organization, determinism, etc. It is determined that the natural scientific picture of the world, in its ecological aspect, is based on V. I. Vernadsky’s doctrine on the biosphere and biogeochemical migration of atoms, N. N. Moiseev’s doctrine on universal evolutionism, and the concept of sustainable development. It is concluded about the role of the natural sciences in the formation of the key concept of sustainable development – the ecological imperative.
Keywords: natural scientific picture of the world; material unity of the world; development; system; self-organization; determinism